Midupper arm circumference and weight-for-length z scores have different associations with body composition: evidence from a cohort of Ethiopian infants–. Issue 3 (29th July 2015) - Grijalva-Eternod, Carlos S; Wells, Jonathan CK; Girma, Tsinuel; Kæstel, Pernille; Admassu, Bitiya; Friis, Henrik; Andersen, Gregers S
ABSTRACT: Background: A midupper arm circumference (MUAC) "115 mm and weight-for-height z score (WHZ) or weight-for-length z score (WLZ) less than −3, all of which are recommended to identify severe wasting in children, often identify different children. The reasons behind this poor agreement are not well understood. Objective: We investigated the association between these 2 anthropometric indexes and body composition to help understand why they identify different children as wasted. Design: We analyzed weight, length, MUAC, fat-mass (FM), and fat-free mass (FFM) data from 2470 measurements from 595 healthy Ethiopian infants obtained at birth and at 1.5, 2.5, 3.5, 4.5, and 6 mo of age. We derived WLZs by using 2006 WHO growth standards. We derived length-adjusted FM and FFM values as unexplained residuals after regressing each FM and FFM against length. We used a correlation analysis to assess associations between length, FFM, and FM (adjusted and nonadjusted for length) and the MUAC and WLZ and a multivariable regression analysis to assess the independent variability of length and length-adjusted FM and FFM with either the MUAC or the WLZ as the outcome. Results: At all ages, length showed consistently strong positive correlations with the MUAC but not with the WLZ. Adjustment for length reduced observed correlation coefficients of FM and FFM with the MUAC but increased those for the WLZ. At all ages, both length-adjusted FM and FFM showed an independent association with the WLZ and MUAC with higher regression coefficients for the WLZ. Conversely, length showed greater regression coefficients for the MUAC. At all ages, the MUAC was shown to be more influenced than was the WLZ by the FM variability relative to the FFM variability. Conclusions: The MUAC and WLZ have different associations with body composition, and length influences these associations differently. Our results suggest that the WLZ is a good marker of tissue masses independent of length. The MUAC acts more as a composite index of poor growth indexing jointly tissue masses and length. This trial was registered at www.controlled-trials.com as ISRCTN46718296.